Criminal Prosecution of Persons, Who Committed Criminal, Acts Using the Сryptocurrency in the Russian Federation - Victorovich Pushkarev, Viktor (2020)
The law enforcement agencies' main focus aimed at combatting crimes, which were committed with the use of cryptocurrency include struggling and prevention of illegal entrepreneurship, illegal banking activity, tax crime, illegal capital outflows, drug business, terrorism financing, legalization (laundering) of income. These crimes are significantly urgent not only in the Russian Federation, but in the whole world, as they provide further criminal economy's and corresponding institutions' development (ie corruption, illegal immigration, etc.). Thus, the topicality and practical importance of elaborating the methods aimed at crime investigation are doubtless.